National hero - Kakutsa Cholokashvili - Maia Burdiashvili (Genius Journals, 2021)
Happy are the people who have worthy sons to be proud of. The national hero is the pride of the past, present and future of the country, he carries his heavy burden with dignity before his homeland and his people. It is such people who leave an indelible mark on the self-consciousness of the people, create history and influence the formation of the future generation. But it often happens that rumors and different views about famous people negatively tune society, as a result of which the heroic deeds committed by them are in the shadows for ten years. Only time and radical changes in political beliefs make it possible to correctly assess personalities and certain phenomena. With the help of this, society receives an impetus for the revaluation of values and in the future, it can already pay tribute to its heroes
Keywords: Homeland; National Liberation Movement; Kakutsa Cholokashvili; World War I